2005
DOI: 10.1111/j.1365-3040.2005.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐induced repression of the rice anther‐specific cell wall invertase gene OSINV4 is correlated with sucrose accumulation and pollen sterility

Abstract: Low temperatures during rice ( Oryza sativa L.) pollen development cause pollen sterility and decreased grain yield. We show that the time of highest sensitivity to cold coincides with the time of peak tapetal activity: the transition of the tetrad to early uni-nucleate stage (young microspore, YM stage). Low temperatures at this stage of pollen development result in an accumulation of sucrose in the anthers, accompanied by decreased activity of cell wall bound acid invertase and depletion of starch in mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
337
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(351 citation statements)
references
References 69 publications
(138 reference statements)
12
337
1
1
Order By: Relevance
“…Intra-specific variability has indeed been extensively reported in cultivated plant species for many reproductive characteristics. Genotype-specific responses have been reported for stress applied during microsporogenesis affecting carbohydrate metabolism, degeneration of the tapetal tissues, pollen wall architecture, pollen morphology, pollen viability, anther dehiscence and pollen production (Aloni et al, 2001;Koti et al, 2005;Oliver et al, 2005;Porch and Jahn, 2001;Prasad et al, 2006;Pressman et al, 2002;Srinivasan et al, 1999;Suzuki et al, 2001). At the post-anthesis level, pollen germination (Hedhly et al, 2005a;Kakani et al, 2002Kakani et al, , 2005, pollen tube growth rate (Clarke and Siddique, 2004;Hedhly et al, 2004;Srinivasan et al, 1999), and pollen dynamics (Hedhly et al, 2005a) also show genotype-specific responses.…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-specific variability has indeed been extensively reported in cultivated plant species for many reproductive characteristics. Genotype-specific responses have been reported for stress applied during microsporogenesis affecting carbohydrate metabolism, degeneration of the tapetal tissues, pollen wall architecture, pollen morphology, pollen viability, anther dehiscence and pollen production (Aloni et al, 2001;Koti et al, 2005;Oliver et al, 2005;Porch and Jahn, 2001;Prasad et al, 2006;Pressman et al, 2002;Srinivasan et al, 1999;Suzuki et al, 2001). At the post-anthesis level, pollen germination (Hedhly et al, 2005a;Kakani et al, 2002Kakani et al, , 2005, pollen tube growth rate (Clarke and Siddique, 2004;Hedhly et al, 2004;Srinivasan et al, 1999), and pollen dynamics (Hedhly et al, 2005a) also show genotype-specific responses.…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%
“…cell wall and vacuolar invertase, sucrose synthase) and transport, are gaining higher research interest as indicators of losses in pollen viability due to temperature fluctuations. Both cold (Oliver et al, 2005) and heat stress (Pressman et al, 2006;Sato et al, 2006) have been shown to down regulate gene expression of several invertase and sucrose synthase isomorphs, and this inhibition was accompanied by a disruption of sucrose and starch…”
Section: Male Development: Pollen Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…heat stressed pistil pollinated with fresh pollen and vice versa wherein female reproductive organ did not reduce fertility even with 40 C exposure, whereas pollen exposed to 38 C led to a significant decline in spikelet fertility (Yoshida et al 1981). Further, the majority of the physiological or molecular studies dealing with microsporogenesis have drawn conclusions based on a single genotype (Kerim et al 2003;Hobo et al 2008;Oliver et al 2005Oliver et al , 2007Endo et al 2009). We hypothesise that spikelet size (length) coinciding with microsporogenesis varies with genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Microsporogenesis, the highly sensitive stage to heat stress (Matsui et al 2000), has not been studied extensively due to the lack of a precise phenotypic marker. However, a marker based on inter auricle distance has been identified for cold stress phenotyping (Satake and Hayase 1970), and extended to quantify the impact of cold (Oliver et al 2005(Oliver et al , 2007 and drought stress (Ji et al 2010;Liu and Bennett 2011) during young microspore and bi-nucleate pollen stages. The classic work by Satake and Hayase (1970) used different inter auricle distances and stress exposure duration to examine just two contrasting rice entries, indicating the challenge in identifying a robust marker that could be used across many genotypes.…”
Section: Introductionmentioning
confidence: 99%